A chronological perspective of telecommunications infrastructure development in India - Malhotra, Charru (2001)
A number of policy decisions and bold initiatives have brought the telecommunication sector out of the clutches of bureaucratic control and pedantic technology. Privatisation of services brought in its wake the need for an effective regulatory hand to ensure level playing field and fair rules for the stakeholders. This article analyses the recent spate of technological activities in the arena and traces the evolution of regulatory mechanisms, introduced through legislative measures, to impart the necessary impetus for a healthy growth of this vital infrastructure. - Reproduced
Keywords: Infrastructure development - India; India - Telecommunication industries; Telecommunications industry